Polyploidy on Islands: Its Emergence and Importance for Diversification - Meudt, Heidi M.; Albach, Dirk C.; Tanentzap, Andrew J.; Igea, Javier; Newmarch, Sophie C.; Brandt, Angela J.; Lee, William G.; Tate, Jennifer A. (Frontiers in Plant Science, 2021)
Whole genome duplication or polyploidy is widespread amongst floras globally, but traditionally has been thought to have played a minor role in the evolution of island biodiversity, based on the low proportion of polyploid taxa present. We investigate five island systems (Juan Fernández, Galápagos, Canary Islands, Hawai'i, and New Zealand) to test whether polyploidy i) enhances or hinders diversification on islands and ii) is an intrinsic feature of a lineage or an attribute that emerges in island environments. These island systems are diverse in their geographic and latitudinal distributions, levels of plant species endemism (37% in the Galapagos to 88% in Hawai'i), and ploidy levels, and taken together are representative of islands more generally. We compiled data for vascular plants and summarized information for each genus on each island system, including total number of species (native and endemic), generic endemicity, chromosome numbers, genome size, and ploidy levels. Dated phylogenies were used to infer lineage age, number of colonization events, and change in ploidy level relative to the non-island sister lineage. Using phylogenetic path analysis, we then tested how the diversification of endemic lineages varied with the direct and indirect effects of polyploidy (presence of polyploidy, time on island, polyploidization near colonization, colonizer pool size) and other lineage traits not associated with polyploidy (time on island, colonizer pool size, repeat colonization). Diploid and tetraploid were the most common ploidy levels across all islands, with the highest ploidy levels (>8x) recorded for the Canary Islands (12x) and New Zealand (20x). Overall, we found that endemic diversification of our focal island floras was shaped by polyploidy in many cases and certainly others still to be detected considering the lack of data in many lineages. Polyploid speciation on the islands was enhanced by a larger source of potential congeneric colonists and a change in ploidy level compared to overseas sister taxa.